Modulation of host antimicrobial peptide (β-defensins 1 and 2) expression during gastritis. Issue 3 (1st September 2002) - Bajaj-Elliott, M; Fedeli, P; Smith, G V; Domizio, P; Maher, L; Ali, R S; Quinn, A G; Farthing, M J G
Abstract : Background: β-Defensins are a newly identified family of antimicrobial peptides that are expressed by epithelia on mucosal surfaces where their production is augmented by infection or inflammation. Helicobacter pylori colonises the gastric epithelium causing persistent gastric inflammation leading to antral and corpus gastritis, and peptic ulcer disease. Aims: To evaluate the role of β-defensins in the innate immune response of the gastric epithelium to infection and inflammation, we have assessed mRNA expression and regulation of human β-defensins 1 and 2 (hBD1, hBD2) by H pylori and proinflammatory stimuli. We have also compared gene and peptide expression of these bactericidal agents in H pylori induced gastritis with that in normal gastric mucosa. Methods: Modulation of expression of hBD1 and hBD2 by various stimuli was studied in three (AGS, MKN7, MKN45) gastric epithelial cell lines by quantitative competitive reverse transcription-polymerase chain reaction (RT-PCR). Defensin mRNA expression was measured by semiquantitative RT-PCR in gastritis tissue and compared with controls. Peptide localisation was assessed by immunohistochemistry. Results: Cytotoxic H pylori and interleukin 1β (IL-1β) markedly upregulated expression of hBD2 in a dose and time dependent manner in both AGS and MKN7 cell lines. A modest increase in hBD1 expression was also noted during infection. Interestingly, induction of hBD1 gene expression by IL-1β was only observed in MKN7 cells. The magnitude of this response was delayed and reduced compared with hBD2 expression. In gastric biopsies, hBD2 was undetectable in normal gastric antrum but a marked increase was observed in H pylori positive gastritis compared with control tissue (p<0.001). Constitutive expression of hBD1 was observed in normal gastric mucosa and there was a significant increase in gastritis (p<0.05). Immunohistochemistry revealed a parallel increase in hBD1 and hBD2 peptide expression in gastritis tissue with positive staining confined to the surface epithelium of the gastric glands. Conclusions: Modulation of β-defensin expression by pathogenic and/or inflammatory stimuli and their cellular localisation places these antimicrobial peptides in the front line of innate host defence in the human stomach.